1993
DOI: 10.1029/93wr00286
|View full text |Cite
|
Sign up to set email alerts
|

Metamodels and nonpoint pollution policy in agriculture

Abstract: Complex mathematical simulation models are generally used for quantitative measurement of the fate of agricultural chemicals in soil. But it is less efficient to use them directly for regional water quality assessments because of the large number of simulations required to cover the entire region and because the entire set of simulation runs must be repeated for each new policy. To make regional water quality impact assessment on a timely basis, a simplified technique called metamodeling is suggested. A metamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Careful data diagnostics were performed to avoid model misspecification and bias. Prior experience in building metamodels for herbicide leaching strongly suggests the need for data transformation to get a good fit (Bouzaher et al, 1993). A linear model for soil erosion indicated that the error terms are non-random, suggesting heteroskedasticity (non-constant variance).…”
Section:  mentioning
confidence: 98%
See 1 more Smart Citation
“…Careful data diagnostics were performed to avoid model misspecification and bias. Prior experience in building metamodels for herbicide leaching strongly suggests the need for data transformation to get a good fit (Bouzaher et al, 1993). A linear model for soil erosion indicated that the error terms are non-random, suggesting heteroskedasticity (non-constant variance).…”
Section:  mentioning
confidence: 98%
“…A simple and scientifically valid statistical procedure for estimating site-specific attributes and aggregating them to regional levels called metamodelling is used. The metamodel is a simple response function fitted to the biogeophysical outputs from calibrated mathematical simulation models (Bouzaher et al, 1993). Lately, the strategy of combining simulation models with mathematical programming models in order to evaluate alternative resource policy scenarios has become the state-of-the-art technique for integrated assessment (Ellis et al, 1991;Wossink et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, integration of the system, whereby an economic activity is temporally and spatially linked with physical phenomena, involves: (1) consistently and robustly linking component models; and (2) aggregating the results into regional indicators of risk and benefits. To ensure congruence of temporal and spatial scale, "experiments" with calibrated geophysical process models produced response surfaces (metamodels) that have statistical integrity and known experimental and sampling error (Bouzaher et al, 1993). Metamodeling abstracts away from unneeded detail for regional analysis by approximating outcomes of a process model through statistically validated response functions, which then allows alternative policy evaluations without the need for additional simulations.…”
Section: The Ceepes Modeling Systemmentioning
confidence: 99%
“…The use of previous versions of PRZi\1 (Bouzaher et al, 1993) demonstrated the need to evaluate the effectiveness of the model by comparing simulations with specific observations of herbicide contamination in grounchvater or soil water. The results of this study will ultimately be used to develop a rnetamodcl similar to that described by Bouzaher et al (1993).…”
Section: Methods and Data Sourcesmentioning
confidence: 99%
“…The results of this study will ultimately be used to develop a rnetamodcl similar to that described by Bouzaher et al (1993). Metamodels, or regression models, will be developed for specific types of aquifers that have been classified and mapped to define potential vulnerability by hydrologic settings (Burkart and Feher, 1996).…”
Section: Methods and Data Sourcesmentioning
confidence: 99%